TRIED IDEAS AND THEIR THREAT TO HUMANITY - Matluba Munavarovna Yuldasheva; Ilkhomova Madinabonu Umidjon kizi (Galaxy International Interdisciplinary Research Journal, 2023)
The article focuses on the threat of terrorism to the historical development of humanity, the genesis of terrorism, the combination of international terrorism and religious extremism that poses a serious threat to international security, peace and tranquility in regions and countries.